2019
DOI: 10.3390/molecules24244581
|View full text |Cite
|
Sign up to set email alerts
|

Anthra[1,2-d][1,2,3]triazine-4,7,12(3H)-triones as a New Class of Antistaphylococcal Agents: Synthesis and Biological Evaluation

Abstract: The development and spread of resistance of human pathogenic bacteria to the action of commonly used antibacterial drugs is one of the key problems in modern medicine. One of the especially dangerous and easily developing antibiotic resistant bacterial species is Staphylococcus aureus. Anthra[1,2-d][1,2,3]triazine-4,7,12(3H)-triones 22–38 have been developed as novel effective antistaphylococcal agents. These compounds have been obtained by sequential conversion of 1-amino-9,10-dioxo-9,10-dihydroanthracene-2-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Some authors revealed 10 to 1000 times lower susceptibility of staphylococcal biofilm to the most common antibiotics [ 10 , 11 ]. Similarly, the outcomes of our recent investigation revealed a much lower susceptibility of S. aureus biofilm towards newly synthesized anthra [1– d ][1,2,3]triazine-4,7,12(3 H )-triones compared to planktonic cells [ 12 ].…”
Section: Introductionmentioning
confidence: 74%
“…Some authors revealed 10 to 1000 times lower susceptibility of staphylococcal biofilm to the most common antibiotics [ 10 , 11 ]. Similarly, the outcomes of our recent investigation revealed a much lower susceptibility of S. aureus biofilm towards newly synthesized anthra [1– d ][1,2,3]triazine-4,7,12(3 H )-triones compared to planktonic cells [ 12 ].…”
Section: Introductionmentioning
confidence: 74%
“…Continuing our research on the search for new substances with practically valuable properties among the functionalized derivatives of 9,10-anthraquinone [19][20][21][22][23], in this work presented herein we report a series of 9,10-anthraquinone derivatives containing dithiocarbamate, thiourea and triazole fragments applied as dyes for the polyester fibers. The sulfur-and nitrogen-containing derivatives 8-18 were prepared via consecutive refunctionalization of aminoanthraquinones 1-7 using methods published in the previous works [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of the previous studies of our group on the functionalization of 9,10-anthracenedione, 36,37,[40][41][42][43][44][45][46] a structural modification of 2-chloro-N-(9,10-dioxo-9,10dihydroanthracene-1(2)-yl)acetamides 1, 2 by pharmacophore fragments, namely, sulfur-containing substituents was carried out. In this work, the reaction of chloroacetamides 1, 2 with a number of alkyl(aryl/hetaroaryl)thiols, additionally functionalised with mercapto, hydroxy, carboxy and carboxylate groups was carried out (Scheme 1).…”
Section: Synthesis Of N-(910-dioxo-910dihydroanthracen-1(2)-yl)-2-(r-...mentioning
confidence: 98%